СТАНОВЛЕНИЕ ЗЕМСКОГО ХОЗЯЙСТВА В КОЛОНИАЛЬНОМ ТУРКЕСТАНЕ (ПО МАТЕРИАЛАМ РЕВИЗИИ СЕНАТОРА К.К.ПАЛЕНА. 1908-1909ГГ.) - Махмудова, Н.Б. (SCIENCE and SOCIETY, 2021)
The article discusses the issues of the formation of “zemsk household” in colonial Turkestan. And the meaning of the concept “zemsk” is highlighted. The differences in the introduction of “zemsk” administration in the Turkestan region and in the Russian Empire are shown. The organization and execution of the approved “zemsk” income and expenditure estimates has been analyzed.